(Invited) Gold Nanobridge Enhanced Fiber Optic Sensor. (23rd August 2016) - Floyd, Adam; Scott, Brian; Song, Yunbin; Fraser, Michael; Yu, Zhihao; Wang, Anbo; Pickrell, Gary
Abstract : We report a method for improving the transmission of a porous capillary tube waveguide gas sensor by applying a thin metallic coating to the inside surface. Using commercially available electroless gold plating solutions and a simple pressure setup, gold thin films were plated on the inner diameter surface of the capillary tube. Nano-porous gold coating was produced during the leaching process used to make the phase separated glass tube porous. Transmission spectra were characterized and determined that to the porous gold coating on the porous glass contributed to signal improvement. Detection of acetylene gas was accomplished but at higher concentrations than uncoated porous capillary tube waveguide. Detection limitations were attributed to lower transmitted power due to optical alignment difficulties.